Service differentiation and inventory management for spare parts in multi-level hierarchical systems - Mouzakitis, Christos (2008)
The after-sales parts sector is a demanding and lucrative business with significant growth the last few years. Often, different groups of customers require different levels of service and this aspect of business is a critical element for the success of their logistics structure. Service differentiation affects inventory decisions as well as the location of service facilities. As a result, inventory decisions need to be made according to different emerging patterns of placement. In such a decentralized environment, inventory availability and cost are the most important features that need to be addressed and optimal solution is given through a trade-off of those two parameters. The research is aiming to study the effects on inventory levels and cost of the different location patterns and then compare the results between an open loop and a closed loop system.